Carotid endarterectomy under local and/or regional anesthesia has less risk of myocardial infarction compared to general anesthesia: An analysis of national surgical quality improvement program database. (April 2015) - Kfoury, Elias; Dort, Jonathan; Trickey, Amber; Crosby, Moira; Donovan, Jean; Hashemi, Homayoun; Mukherjee, Dipankar
Multiple studies have evaluated the effect of anesthesia type on carotid endarterectomy with inconsistent results. Our study compared 30-day postoperative myocardial infarction, stroke, and mortality between carotid endarterectomy under local or regional anesthesia and carotid endarterectomy under general anesthesia utilizing National Surgical Quality Improvement Program database. All patients listed in National Surgical Quality Improvement Program database that underwent carotid endarterectomy under general anesthesia and local or regional anesthesia from 2005 to 2011 were included with the exception of patients undergoing simultaneous carotid endarterectomy and coronary artery bypass grafting. The data revealed substantial differences between the two groups compared, and these were adjusted using multiple logistic regression. Postoperative myocardial infarction, stroke, and death at 30 days were compared between the two groups. A total of 42, 265 carotid endarterectomy cases were included. A total of 37, 502 (88.7%) were performed under general anesthesia and 4763 (11.3%) under local or regional anesthesia. Carotid endarterectomy under local or regional anesthesia had a significantly decreased risk of 30-day postoperative myocardial infarction when compared to carotid endarterectomy under general anesthesia (0.4% vs 0.86%, p = 0.012). No statistically significant differences were found in postoperative stroke or mortality. Carotid endarterectomy under local or regional anesthesia carries a decreased risk of postoperative myocardial infarction when compared to carotid endarterectomy under general anesthesia. Therefore, patients at risk of postoperative myocardial infarction undergoing carotid endarterectomy, consideration of local or regional anesthesia may reduce that risk.